"The Mind Is Its Own Place": Amelioration of Claustrophobia in Semantic Dementia. (6th March 2014) - Clark, Camilla N.; Downey, Laura E.; Golden, Hannah L.; Fletcher, Phillip D.; de Silva, Rajith; Cifelli, Alberto; Warren, Jason D.
Abstract : Phobias are among the few intensely fearful experiences we regularly have in our everyday lives, yet the brain basis of phobic responses remains incompletely understood. Here we describe the case of a 71-year-old patient with a typical clinicoanatomical syndrome of semantic dementia led by selective (predominantly right-sided) temporal lobe atrophy, who showed striking amelioration of previously disabling claustrophobia following onset of her cognitive syndrome. We interpret our patient's newfound fearlessness as an interaction of damaged limbic and autonomic responsivity with loss of the cognitive meaning of previously threatening situations. This case has implications for our understanding of brain network disintegration in semantic dementia and the neurocognitive basis of phobias more generally.